Kesulitan Guru dalam Menyusun Perangkat Pembelajaran Daring pada Kurikulum 2013 di SDN Gugus II Kecamatan Sape - Susanti, Mariani; Zain, Moh. Irawan; Saputra, Heri Hadi (Educational Consultant & Counseling Career (EC3) Mataram, 2022)
The aim of this study is to determine the teachers difficulties in arranging online learning device on the Curirculum 2013 at SDN Gugus II in Sape district. The approach of this research used qualitative methods. Data collection techniques are done by interviewing, observation, and documentation. The result of this study showed the teachers still have some difficulties in arranging learning devices for online learning, namely (1)difficulty in compiling learning scenario consisting of pre activities 65%, while activities 20%, and posts activities 15%; (2) difficulty compiling the material 46,67%; (3) difficulty in making learning media 60%; (4) difficulties in compiling LKPD 50%; and (5)difficulty in formulating learning assessmen 60%. Thus, it was found that the difficulties of teachers in compiling online learning devices were quite varied. In the difficulty of formulating a learning scenario, it was found difficult to determine the time allocation, the suitability of the steps with the learning method; In compiling the material, it was found difficulties in the suitability of the material with the KD-IPK and the completeness of the material; on the difficulty of making media it was found difficult to adapt the media to the KD-IPK, and materials; on difficulties in compiling LKPD found difficulties in adjusting LKPD with KD-IPK, and materials; Then it was also found difficult to formulate a learning assessment, namely the difficulty of completing the assessment instrument in the form of compiling HOTS question grids, HOTS questions, and determining the HOTS rubric score